Green low-carbon expansion joint rapid repair material and preparation method thereof

Through the rapid repair materials of green low-carbon expansion joints prepared by industrial solid waste and agricultural solid waste, the problems of carbon emissions and environmental pollution in the existing technology have been solved, and the ultra-premature strength and impact-resistant repair of bridge expansion joints have been achieved, and the The harmless utilization of industrial solid waste and agricultural solid waste has high promotion and application value.

CN119191801APending Publication Date: 2024-12-27GUIZHOU EXPRESSWAY IND CO LTD GUIYANG BRANCH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411095586.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The preparation process of existing expansion joint rapid repair materials leads to a large amount of carbon emissions and environmental pollution, and it is difficult to effectively utilize industrial solid waste and agricultural solid waste, affecting the health of the bridge structure.

Method used

The green low-carbon expansion joint rapid repair materials prepared by industrial solid waste and agricultural solid waste are realized through the combination of industrial solid waste composite cementitious materials, composite aggregates, green hardener, admixtures and composite fibers. Rapid repair, use industrial solid waste and agricultural solid waste for harmless and resource utilization, and reduce carbon emissions and environmental pollution.

Benefits of technology

It has achieved ultra-premature strength and impact-resistant restoration of bridge expansion joints, with the advantages of green, low-carbon and environmental protection, and has completed the harmless utilization of a variety of industrial solid waste and agricultural solid waste. The materials can be opened to traffic within 2 hours. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004987821750000081
    Figure BDA0004987821750000081
Patent Text Reader

Abstract

The invention relates to a green low-carbon rapid repair material for expansion joints. The green low-carbon rapid repair material comprises the following components in parts by weight: 370-500 parts of an industrial solid waste composite cementing material, 450-550 parts of industrial solid waste composite aggregate, 50-85 parts of a green hardening accelerator, 2.2-3.5 parts of an additive, 4-8 parts of composite fibers and 120-150 parts of water. The green low-carbon expansion joint rapid repair material provided by the invention has the advantages of super early strength, impact resistance, greenness, low carbon, environmental protection and the like. When the green low-carbon expansion joint rapid repair material provided by the invention is used for repairing expansion joints, traffic can be opened only in 2 hours. The invention further provides a preparation method of the repair material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of bridge expansion joint repair, and in particular to a green and low-carbon expansion joint quick repair material and a preparation method thereof. Background Art

[0002] The expansion joint is a boundary condition of the bridge structure, and its health directly affects the stress of the bridge structure. Since the expansion joint is located at the connection of the bridge, it is very easy to generate stress concentration, and the anchorage area is at the weak surface of the junction of the new and old concrete. Under the long-term impact of vehicles, it is very easy to form interlayer shear fatigue failure. Therefore, during the long-term operation of the bridge, the concrete in the anchorage area of ​​the expansion joint is frequently damaged.

[0003] At present, the existing technologies mostly prepare expansion joint quick repair materials by adding aggregates, polymers, fibers, admixtures, etc. to cement-based materials. However, the raw materials and preparation processes of these materials will cause a large amount of carbon emissions and serious environmental pollution. At the same time, with the rapid development of society, the treatment of industrial solid waste and agricultural solid waste has become a prominent problem in the process of environmental governance. Therefore, it is urgent and necessary to carry out the harmless and resource utilization of industrial solid waste and agricultural solid waste, and reduce the environmental pollution and carbon emissions caused by the preparation of traditional expansion joint quick repair materials. Summary of the invention

[0004] In view of one of the defects existing in the prior art, the purpose of the present invention is to provide a green and low-carbon expansion joint quick repair material and a preparation method thereof, which can realize the rapid repair of bridge expansion joints through the harmless and resource utilization of industrial solid waste and agricultural solid waste, and has the advantages of ultra-early strength, impact resistance, green, low carbon and environmental protection.

[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is:

[0006] The invention provides a green and low-carbon expansion joint quick repair material, comprising the following components in parts by weight: 370-500 parts of industrial solid waste composite cementitious materials, 450-550 parts of industrial solid waste composite aggregates, 50-85 parts of green hardening accelerators, 2.2-3.5 parts of admixtures, 4-8 parts of composite fibers, and 120-150 parts of water.

[0007] On the basis of the above scheme, the industrial solid waste cementitious material includes silicate cement, sulphoaluminate cement, and industrial solid waste components, and the mass ratio thereof is 1:0.12:0.6; the industrial solid waste components in the industrial solid waste cementitious material include alkali slag, slag, steel slag, desulfurized gypsum, silica fume, and fly ash, and the mass ratio thereof is 1:1.5:0.5:0.3:0.1:0.06. Alkali slag, slag, steel slag, and desulfurized gypsum undergo hydration reaction to generate hydrated calcium silicate gel, calcium sulfonate, Fred salt, and calcium carbonate. Calcium sulfonate, Fred salt, calcium carbonate, and silica fume are used as filling materials for hydrated calcium silicate gel to increase the density of the slurry and improve the strength of the material. The addition of fly ash can improve the fluidity of the material. Through the synergistic reaction of multiple industrial solid wastes, each industrial solid waste synergistic component can maximize its own advantages, increase the utilization efficiency of industrial solid waste, reduce the amount of silicate cement and sulphoaluminate cement, and achieve the purpose of green, low-carbon, and environmental protection.

[0008] Preferably, the strength grade of the silicate cement is 52.5; the strength grade of the sulphoaluminate cement is 42.5; the alkali residue is a powder formed by grinding and drying the waste residue produced in the process of preparing soda ash by the ammonia-alkali method, and the specific surface area is 330-370m 2 / kg, the moisture content is 28-43%, the main chemical components are calcium oxide, magnesium oxide, silicon dioxide; the slag is a powder formed by grinding and drying blast furnace water-quenched slag, with a surface area of ​​455-510m 2 / kg, the basicity coefficient is 0.96-0.99, and the main chemical components are calcium oxide, aluminum oxide, and silicon dioxide; the steel slag is a powder formed by grinding and drying the converter hot-stewed steel slag, and the specific surface area is 475-525m 2 / kg, the main chemical components are dicalcium silicate, dicalcium ferrite, and tricalcium chlorate; the desulfurization gypsum is a powder formed by grinding and drying the solid waste generated by the wet limestone-gypsum desulfurization process of a thermal power plant, with a specific surface area of ​​380-420m 2 / kg, the main chemical component is calcium sulfate dihydrate; the specific surface area of ​​the silica ash is greater than 16000m 2 / kg, the silicon dioxide content is greater than 90%; the fly ash is Class F Grade I fly ash.

[0009] On the basis of the above scheme, the industrial solid waste aggregate includes quartz sand, glass sand, and graphite tailings sand, and the mass ratio thereof is 1:0.4:0.3. The use of glass sand and graphite tailings sand to replace part of quartz sand not only reduces the environmental problems caused by the quartz sand mining process, but also makes harmless and resource-based utilization of industrial solid wastes such as waste glass and graphite tailings sand, and has the advantages of being green, low-carbon, and environmentally friendly.

[0010] Preferably, the quartz sand has a particle size of 0.35 to 0.5 mm.

[0011] Preferably, the glass sand is processed from waste glass and has a particle size of 0.20 to 0.35 mm.

[0012] Preferably, the graphite tailings are waste generated from graphite development, the main chemical components of which are silicon dioxide, aluminum oxide, iron oxide, and calcium oxide, and the particle size is 0.05 to 0.20 mm.

[0013] On the basis of the above scheme, the green hardening accelerator is an impurity-free hydrated calcium silicate crystal hardening accelerator synthesized from agricultural waste bagasse ash as raw material, which has the characteristics of being green and environmentally friendly. The preparation method thereof is as follows: treating bagasse ash with a sodium hydroxide solution at 100°C, and extracting amorphous silicon dioxide present on the surface of bagasse ash in the form of a sodium silicate solution. After preparing a sodium silicate solution using bagasse ash as raw material, an ion exchange method is used to react the sodium silicate solution with a calcium solution in the presence of a dispersant polyethylene glycol to prepare a hardening accelerator containing tiny hydrated calcium silicate crystals.

[0014] On the basis of the above scheme, the admixture includes a water reducer and a retarder, and the mass ratio thereof is 1:0.28.

[0015] Preferably, the water reducer is a high-efficiency polycarboxylic acid water reducer, and the retarder is a mixture of tartaric acid and boric acid in a mass ratio of 6:4.

[0016] On the basis of the above scheme, the composite fiber includes steel fiber, polypropylene fiber and Artemisia selengensis plant fiber, and the mass ratio thereof is 1:0.16:0.13. Artemisia selengensis plant fiber is a natural plant fiber, and the use of Artemisia selengensis plant fiber to replace part of steel fiber and polypropylene fiber reduces the carbon emission and environmental pollution problems caused by the production of steel fiber and polypropylene fiber, and achieves the purpose of green, low-carbon and environmental protection.

[0017] Preferably, the steel fiber has a diameter of 0.15 mm, a length of 12 mm, and a tensile strength higher than 1800 MPa.

[0018] Preferably, the polypropylene fiber is 10 μm in diameter, 8 mm in length, and has a tensile strength higher than 1100 MPa.

[0019] Preferably, the Artemisia annua plant fiber is 0.5 mm thick, 20 mm long, and has a tensile strength higher than 600 MPa. The preparation method is to cut the Artemisia annua peel into 20 mm lengths, soak it in a 1% sodium hydroxide solution for 30 minutes, remove it, rinse it with clean water, and dry it naturally in the shade.

[0020] The present invention also provides a method for preparing a green and low-carbon expansion joint quick repair material, comprising the following steps:

[0021] S1. Add the industrial solid waste composite cementitious material and industrial solid waste composite aggregate designed according to the ratio into the mixer and stir at low speed for 3 minutes;

[0022] S2. Add equal amounts of water, green hardening accelerator and admixture into the mixer in two batches, stirring for 2 minutes each time.

[0023] S3. Divide the composite fiber into five equal parts. After the slurry is formed, sprinkle the composite fiber evenly in equal amounts every minute and stir for 5 minutes.

[0024] S4. Place the slurry into the expansion joint anchoring area, vibrate it evenly within 5 minutes, smooth and plaster the surface, and open it to traffic after 2 hours.

[0025] Compared with the prior art, the green and low-carbon expansion joint quick repair material provided by the present invention has the advantages of super early strength, impact resistance, green, low carbon, and environmental protection. While realizing the rapid repair of bridge expansion joints, it also completes the harmlessness and resource utilization of various industrial solid wastes and agricultural solid wastes such as alkali slag, slag, steel slag, desulfurized gypsum, silica ash, fly ash, waste glass, graphite tailings sand, and bagasse ash. The use of natural plant fibers to replace part of steel fibers and polypropylene fibers further improves the advantages of the material in terms of low carbon and environmental protection. It only takes 2 hours to open traffic to the expansion joints by using the green and low-carbon expansion joint quick repair material provided by the present invention to repair the expansion joints. DETAILED DESCRIPTION

[0026] The embodiments of the present invention are described in detail below. The following embodiments are implemented on the premise of the scheme of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.

[0027] Table 1

[0028] Components Example 1 Example 2 Example 3 Example 4 Example 5 Industrial solid waste composite cementitious materials 100 copies 100 copies 100 copies 100 copies 100 copies Industrial solid waste composite aggregate 95 copies 113 copies 125 servings 133 copies 145 copies Green hardening agent 12 servings 15 servings 15 servings 15 servings 20 servings Admixtures 0.7 parts 0.8 parts 0.9 parts 0.8 parts 0.9 parts Composite Fiber 1.6 servings 2 servings 1.5 servings 1.5 servings 1.2 servings water 28 servings 30 servings 32 servings 32 servings 38 servings .

[0029] As shown in Table 1, the green low-carbon expansion joint quick repair material provided in Examples 1 to 5 is prepared by the following method using industrial solid waste composite cementitious material, industrial solid waste composite aggregate, green hardening accelerator, admixture, composite fiber, and water according to the proportions in Table 1:

[0030] S1. Add the industrial solid waste composite cementitious material and industrial solid waste composite aggregate designed according to the ratio into the mixer and stir at low speed for 3 minutes;

[0031] S2. Add equal amounts of water, green hardening accelerator and admixture into the mixer twice, stirring for 2 minutes each time; that is, after the first addition, stir for 2 minutes, then add the second addition, and continue stirring for 2 minutes.

[0032] S3. Divide the composite fiber into five equal parts, and after the slurry prepared in step 2 is formed, sprinkle the composite fiber evenly in equal amounts every minute and stir for 5 minutes; that is, after the slurry prepared in step 2 is formed, add the composite fiber in five times, and stir for 1 minute after each addition of the composite fiber.

[0033] S4. Place the slurry prepared in step 4 in the expansion joint anchoring area, vibrate it evenly within 5 minutes, smooth and plaster it, and open it to traffic after 2 hours.

[0034] In a preferred embodiment, the industrial solid waste cementitious material includes silicate cement, sulphoaluminate cement, and industrial solid waste components, and the mass ratio thereof is 1:0.12:0.6; the industrial solid waste components in the industrial solid waste cementitious material include alkali slag, slag, steel slag, desulfurized gypsum, silica fume, and fly ash, and the mass ratio thereof is 1:1.5:0.5:0.3:0.1:0.06. Alkali slag, slag, steel slag, and desulfurized gypsum undergo hydration reaction to generate hydrated calcium silicate gel, calcium sulfonate, Fred salt, and calcium carbonate. Calcium sulfonate, Fred salt, calcium carbonate, and silica fume are used as filling materials for hydrated calcium silicate gel to increase the density of the slurry and improve the strength of the material. The addition of fly ash can improve the fluidity of the material. Through the synergistic reaction of multiple industrial solid wastes, each industrial solid waste synergistic component can maximize its own advantages, increase the utilization efficiency of industrial solid waste, reduce the amount of silicate cement and sulphoaluminate cement, and achieve the purpose of green, low-carbon, and environmental protection.

[0035] In a preferred embodiment, the strength grade of the silicate cement is 52.5; the strength grade of the sulphoaluminate cement is 42.5; the alkali residue is a powder formed by grinding and drying the waste residue produced in the process of preparing soda ash by the ammonia-alkali method, and the specific surface area is 345m 2 / kg, with a moisture content of 31%, and the main chemical components are calcium oxide, magnesium oxide, and silicon dioxide; the slag is a powder formed by grinding and drying blast furnace water-quenched slag, with a specific surface area of ​​483m 2 / kg, the basicity coefficient is 0.98, and the main chemical components are calcium oxide, aluminum oxide, and silicon dioxide; the steel slag is a powder formed by grinding and drying the converter hot-stewed steel slag, with a specific surface area of ​​491m 2 / kg, the main chemical components are dicalcium silicate, dicalcium ferrite, and tricalcium chlorate; the desulfurization gypsum is a powder formed by grinding and drying the solid waste generated by the wet limestone-gypsum desulfurization process of a thermal power plant, with a specific surface area of ​​398m 2 / kg, the main chemical component is calcium sulfate dihydrate; the specific surface area of ​​the silica ash is 18500m 2 / kg, with a silicon dioxide content of 92%; the fly ash is Class F Grade I fly ash.

[0036] In a preferred embodiment, the industrial solid waste aggregate includes quartz sand, glass sand, and graphite tailings sand, with a mass ratio of 1:0.4:0.3; the quartz sand has a particle size of 0.35-0.5 mm; the glass sand is processed from waste glass, with a particle size of 0.20-0.35 mm; the graphite tailings sand is a waste formed by graphite development, with the main chemical components of silicon dioxide, aluminum oxide, iron oxide, and calcium oxide, and a particle size of 0.05-0.20 mm. Using glass sand and graphite tailings sand to replace part of quartz sand not only reduces the environmental problems caused by the quartz sand mining process, but also makes harmless and resource-based utilization of industrial solid wastes such as waste glass and graphite tailings sand, which has the advantages of being green, low-carbon, and environmentally friendly.

[0037] In a preferred embodiment, the green hardening accelerator is an impurity-free calcium silicate hydrate crystal hardening accelerator synthesized from agricultural waste bagasse ash as raw material, which has the characteristics of being green and environmentally friendly, and can be prepared by the following method:

[0038] S1. treating bagasse ash with a sodium hydroxide solution at 100° C. to extract amorphous silica present on the surface of bagasse ash in the form of a sodium silicate solution;

[0039] S2. After preparing a sodium silicate solution using bagasse ash as a raw material, the sodium silicate solution is reacted with a calcium solution by an ion exchange method in the presence of a dispersant, polyethylene glycol, to prepare a hardening accelerator containing tiny hydrated calcium silicate crystals.

[0040] Preferably, the admixture includes a water reducer and a retarder in a mass ratio of 1:0.28; the water reducer is a high-efficiency polycarboxylic acid water reducer, and the retarder is a mixture of tartaric acid and boric acid in a mass ratio of 6:4.

[0041] Preferably, the composite fiber includes steel fiber, polypropylene fiber, and artemisia selengensis plant fiber, and the mass ratio is 1:0.16:0.13; the steel fiber has a diameter of 0.15 mm, a length of 12 mm, and a tensile strength of 2000 MPa; the polypropylene fiber is 10 μm, a length of 8 mm, and a tensile strength of 1200 MPa; the artemisia selengensis plant fiber is 0.5 mm, and a length of about 20 mm. By conducting a tensile strength test on a universal testing machine, the tensile strength is measured to be about 700 MPa. The preparation method is to cut the artemisia selengensis peel into 20 mm lengths and then place it in a 1% sodium hydroxide solution and soak it for 30 minutes, remove it and rinse it with clean water, and dry it naturally in the shade. Artemisia selengensis plant fiber is a natural plant fiber. Artemisia selengensis plant fiber is used to replace part of steel fiber and polypropylene fiber, which reduces the carbon emissions and environmental pollution problems caused by the production of steel fiber and polypropylene fiber, and achieves the purpose of green, low-carbon and environmental protection.

[0042] According to the requirements of "Rapid Repair Materials for Cement Concrete in Highway Engineering" (JT / T1211.2-2019), the green low-carbon expansion joint rapid repair materials prepared in Examples 1 to 5 were tested for performance, and the results are shown in Table 2:

[0043] Table 2

[0044]

[0045] As shown in Table 2, the green and low-carbon expansion joint quick repair materials prepared in Examples 1 to 5 have the advantages of super early strength and impact resistance, and the 2-hour compressive and flexural strengths reach 33MPa and 6.3MPa or more, respectively, meeting the requirements of CRRM-II materials in "Rapid Repair Materials for Cement Concrete in Highway Engineering" (JT / T1211.2-2019), and traffic can be opened after 2 hours of maintenance. At the same time, the material uses a large amount of industrial solid waste, agricultural solid waste and natural green materials, has the advantages of green and low carbon, and has a high value of promotion and application.

[0046] It should be noted that, in this application, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "includes a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0047] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A green and low-carbon expansion joint quick repair material, characterized in that: It includes the following components in parts by weight: 370-500 parts of industrial solid waste composite cementitious materials, 450-550 parts of industrial solid waste composite aggregates, 50-85 parts of green hardening accelerators, 2.2-3.5 parts of admixtures, 4-8 parts of composite fibers, and 120-150 parts of water.

2. A green and low-carbon expansion joint quick repair material as claimed in claim 1, characterized in that: The industrial solid waste cementitious material includes silicate cement, sulfoaluminate cement, and industrial solid waste components, and their mass ratio is 1:0.12:0.6; the industrial solid waste components in the industrial solid waste cementitious material include alkali slag, slag, steel slag, desulfurized gypsum, silica fume, and fly ash, and their mass ratio is 1:1.5:0.5:0.3:0.1:0.06:0.

01.

3. A green and low-carbon expansion joint quick repair material as claimed in claim 2, characterized in that: The strength grade of silicate cement is 52.5; the strength grade of sulphoaluminate cement is 42.5; the alkali residue is the waste residue produced in the process of preparing soda ash by ammonia-alkali method, which is ground and dried to form a powder, and the specific surface area is 330~370m 2 / kg, moisture content is 28~43%,; The slag is a powder formed by grinding and drying blast furnace water-quenched slag, with a specific surface area of ​​455~510m 2 / kg, the basicity coefficient is 0.96~0.99, the steel slag is the powder formed by grinding and drying the converter hot-stewed steel slag, and the specific surface area is 475~525m 2 / kg,; the desulfurized gypsum is a powder formed by grinding and drying the solid waste produced by the wet limestone-gypsum desulfurization process of a thermal power plant, with a specific surface area of ​​380~420m 2 / kg,; the specific surface area of ​​the silica ash is greater than 16000m 2 / kg, with a silicon dioxide content of more than 90%; the fly ash is Class F Grade I fly ash.

4. The green and low-carbon expansion joint quick repair material according to claim 1, characterized in that: The industrial solid waste aggregate includes quartz sand, glass sand and graphite tailings sand, and the mass ratio thereof is 1:0.4:0.

3.

5. A green and low-carbon expansion joint quick repair material as claimed in claim 4, characterized in that: The quartz sand has a particle size of 0.35-0.5 mm; the glass sand is processed from waste glass and has a particle size of 0.20-0.35 mm; the graphite tailings sand is waste formed by graphite development, and its main chemical components are silicon dioxide, aluminum oxide, iron oxide, and calcium oxide, and its particle size is 0.05-0.20 mm.

6. The green and low-carbon expansion joint quick repair material according to claim 1, characterized in that: The green hardening accelerator is an impurity-free hydrated calcium silicate crystal hardening accelerator synthesized with agricultural waste bagasse ash as raw material.

7. The green and low-carbon expansion joint quick repair material according to claim 1, characterized in that: The admixture includes a water reducer and a retarder in a mass ratio of 1:0.

28. The water reducer is a high-efficiency polycarboxylic acid water reducer, and the retarder is a mixture of tartaric acid and boric acid in a mass ratio of 6:

4.

8. The green low-carbon expansion joint quick repair material according to claim 1, characterized in that: The composite fiber includes steel fiber, polypropylene fiber and Artemisia annua plant fiber, and the mass ratio thereof is 1:0.16:0.

13.

9. A green and low-carbon expansion joint quick repair material as claimed in claim 8, characterized in that: The steel fiber has a diameter of 0.15 mm, a length of 12 mm, and a tensile strength of more than 1800 MPa; the polypropylene fiber has a diameter of 10 μm, a length of 8 mm, and a tensile strength of more than 1100 MPa; the Artemisia annua plant fiber has a diameter of 0.5 mm, a length of 20 mm, and a tensile strength of more than 600 MPa.

10. A method for preparing the green low-carbon expansion joint quick repair material according to claim 1, characterized in that: The following steps are involved: S1. Add the designed industrial solid waste composite cementitious material and industrial solid waste composite aggregate into the mixer and stir at low speed for 3 minutes; S2. Add equal amounts of water, green hardening agent and admixture into the mixer twice, stirring for 2 minutes each time; S3. Divide the composite fiber into five equal parts. After the slurry is formed, sprinkle the composite fiber evenly in equal amounts every minute and stir for 5 minutes. S4. Place the slurry into the expansion joint anchorage area, vibrate it evenly within 5 minutes, smooth and plaster the surface, and open it to traffic after 2 hours.